IMPLEMENTASI PROGRAM BERAS MISKIN DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KELURAHAN TELUK UMA - Zulkarnain, Deska (Menara Ilmu, 2018)
Raskin program is a program of government. The program is implemented under the responsibility of the Ministry of Home Affairs and Bulog in accordance with the Joint Decree of the Minister of Home Affairs with the President Director of Bulog Number: 25 Year 2003 and Number: PKK-12/07/2003, involving the relevant Government Institution Areas and communities.Raskin program aims to reduce the burden of spending from poor households as a form of support in improving food security by providing social protection, cheap rice with a maximum of 15 Kg / RTM / month with each for Rp. 1.600 / Kg (Netto) at the distribution point. The program covers all provinces, while the responsibility of rice distribution from warehouse to distribution point is held by Bulog.The purpose of this research is to know the policy of raskin program and to know the implementation of Raskin program in Teluk Uma Urban whether to run in accordance with Raskin general guidance. While this research using George C. Edward III theory. This research method is descriptive method with qualitative approach. Descriptive method is the method of focusing attention to the problems or phenomena that existed at the time this research is done, while the data analysis technique of this study using qualitative techniques that is the analysis of data obtained based on the ability of researchers in connecting facts, and information.